Validation and cross-cultural adaptation of the Brazilian Portuguese version of the questionnaire for the assessment of pelvic floor disorders and their risk factors during pregnancy and postpartum - Vieira, Renata Cristina Martins da Silva; Silva, Jordana Barbosa da; Cavalli, Ricardo de Carvalho; Driusso, Patricia (Universidade Federal de São Carlos, 2022)
Introduction and hypothesis Pelvic floor dysfunction may be treated and prevented during pregnancy and postpartum, as it decreases women’s quality of life. The aim of the present study was to translate and validate the Brazilian Portuguese questionnaire for the assessment of pelvic floor disorders and their risk factors during pregnancy and postpartum. Methods This is a cross-sectional study. Two translators fluent in German translated the German version of the questionnaire into English. The back translation was performed by two other translators. The final version was tested on Brazilian pregnant/puerperal women. The participants answered the questionnaire twice, with an interval of 7–10 days between sessions. They also completed the Medical Outcomes Study 36-Item Short-Form Health Survey (SF-36). To evaluate the test–retest reliability, we used the intraclass correlation coefficient (ICC), Cronbach's alpha coefficient, to test the internal consistency, and Pearson's linear correlation to assess construct validity. Results Sixty-six women were included (77% pregnant; 23% puerperal women), with a mean age of 26.5 ± 5.8 years and a body mass index of 26.4 ± 5.7 kg/cm2. There were no missing ceiling or floor effects. The construct validity presented a moderate correlation with the role physical domain of the SF-36 (r = −0.48), the ICC test–retest showed good reliability of 0.72, and the internal consistency was 0.71. Conclusions These results provide evidence that the questionnaire for the assessment of pelvic floor disorders and their risk factors during pregnancy and postpartum is a valid and reliable instrument when utilized in Brazilian pregnant and postpartum women.
Keywords: Urinary incontinence; Health education; Physical therapy specialty; Women’s health; CIENCIAS DA SAUDE::MEDICINA::CLINICA MEDICA::GINECOLOGIA E OBSTETRICIA